DESIGN MUDMAT AND PILE FOUNDATION OF JACKET OFFSHORE PLATFORM USING LINEAR ANALYSIS FOR IN-PLACE CONDITION - Albertus
Offshore platform is a special platform commonly used for exploration and production activities in offshore area. This structure can be separated into fixed and floating type platform. Fixed jacket platform has two types of foundation, which are mudmat and pile foundation. Mudmat is a shallow foundation designed to support jacket structure due to environment load during installation process of the structure, meanwhile pile foundation is the main foundation in offshore platform which driven into the jacket’s leg. The design of mudmat obtained from iteration process of material dimension and material specification considering the working load applied. Calculation and analysis of mudmat capacity are based on these conditions: bearing failure, sliding failure, allowable stress, and local squeezing. First, the bearing failure condition determined by setting overturning point location based on the direction of environment force. Second, soil’s ultimate shear resistance at undrained condition checked using the sliding failure. Third, to know whether the soil stress can resist external stress due to loading, the allowable stress is used. Finally, the local squeezing condition can be observed using a hollow configuration (without plate). Those conditions mentioned must comply minimum safety factor recommended by API RP 2A as the main standard of offshore building design. The design of pile acquired by using linear analysis for inplace condition. Inplace analysis is the platform’s serviceability analysis that consider two conditions: operating and storm. Output which obtained from this analysis are pile’s axial and lateral capacity. The calculation of axial capacity determined by using ? - method, whereas lateral capacity calculated automatically by software. Next, actual stress and minimum deflection that occur on the pilehead is checked. Those stress and deflection must not exceed the pile’s allowable capacity, which is controlled by the unity check parameter. Finally, pile driveability is used in determining hammer specification, blow count, and actual stress during driving activity.